Optimasi Produktivitas di Brightness Bakery & Cake: Strategi Pengukuran Kerja untuk Standarisasi Waktu - Sihar, Ojakma; Supriyono, Supriyono; Wismantoro, Sindhu; Agung, Kurniawan; Fatoni, Ahmad (JITMI (Jurnal Ilmiah Teknik dan Manajemen Industri), 2024)
Efficiency in work is identified through fast completion with high quality. Working time measurement is an evaluation tool to assess the duration required by an experienced operator to complete a task. The aim of this research is to determine the use of study methods in measuring work, to determine the amount of normal time and standard time. Data collection method obtained directly from the measurements taken. Meanwhile, the data analysis method uses the time study method. The results of this research are for calculating standard time in the bread production process using the Factor rating based on the Westinghouse table which is 014 so that the total normal time (Wn) obtained is 249.39 minutes for the eight work elements. In calculating the standard time (Wb), the company's policy allowance factor is 5% (0.05) so that the standard time obtained is 261.85 minutes for one production batch. Keywords: Production Efficiency, Production Time, Normal Time, Standard Time